Unraveling Interactions of the Necrotrophic Fungal Species Botrytis cinerea With 1-Methylcyclopropene or Ozone-Treated Apple Fruit Using Proteomic Analysis - Testempasis, Stefanos; Tanou, Georgia; Minas, Ioannis; Samiotaki, Martina; Molassiotis, Athanassios; Karaoglanidis, Georgios (Frontiers in Plant Science, 2021)
Gray mold caused by the necrotrophic fungus Botrytis cinerea is one of the major postharvest diseases of apple fruit. The exogenous application of 1-methylcyclopropene (1-MCP) and gaseous ozone (Ο3) is commonly used to ensure postharvest fruit quality. However, the effect of these treatments on the susceptibility of apple fruit to postharvest pathogens remains largely unknown. Herein, the effect of Ο3 and 1-MCP treatments on the development of gray mold on apple fruit (cv. “Granny Smith”) was investigated. Artificially inoculated apple fruit, treated or not with 1-MCP, subjected for 2 months to cold storage (0 oC, RH 95%) either in an O3-enriched atmosphere or in a conventional cold chamber. Minor differences between 1-MCP-treated and control fruits were found in terms of disease expession, however, exposure to ozone resulted in a decrease of disease severity by more than 50% compared to 1-MCP-treated and untreated fruit. Proteomic analysis was conducted to determine proteome changes in the mesocarp tissue of control and 1-MCP- or O3-treated fruit in the absence or in the presence of inoculation with B. cinerea. In the non-inoculated fruit, 26 proteins were affected by 1-MCP, while 51 proteins were altered by ozone. Dynamic changes in fruit proteome were also observed in response to B. cinerea. In O3-treated fruit, a significant number of disease/defense-related proteins was increased in comparison to control fruit. Among these proteins higher accumulation levels were observed for allergen, major allergen, ACC oxidase, Putative NBS-LRR disease resistance protein, MLP-like protein or 2-Cys peroxiredoxin. In contrast, most of these proteins were downaccumulated in 1-MCP-treated fruit that challenged with B. cinerea. These results suggest that ozone exposure may contribute to the reduction of gray mold in apple fruit, while 1-MCP was not effective in affecting this disease. This is the first study deciphering differential regulations of apple fruit proteome upon B. cinerea infection and postharvest storage treatments, elucidating resistance responses.